Desiring the beautiful: the erotic-aesthetic dimension of deification in Dionysius the Areopagite and Maximus the Confessor - Ivanović, Filip (Catholic University of America Press, 2019)
Dionysius the Areopagite -- Love -- Beauty -- Deification -- Maximus the Confessor -- Love -- Beauty -- Deification -- Love and beauty in deification.